Perancangan Prototipe Rain Drop Sensor Berbasis Arduino Uno - Hendry; Chairul Rizal; Supiyandi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In Indonesia, the climate is mostly hot and humid, and most of the rainfall occurs. As a result, people are less aware of how much rain occurs inside rooms, homes, and offices. We need a warning to explain the problem so that we can take the necessary action when it rains. By creating Arduino-based rain sensors and implementing the fourth industrial revolution in everyday life, the study aims to raise awareness of rain unknowingly. The initial method is the implementation of the Raindrop Sensor based arduino which is an Arduino standard board based on the ATmega328P microcontroller. The Rain Drop Sensor Module works when it rains, when the electric vibration buzzer rains into sound vibration, then the buzzer will provide sound information. The research results of the sensor value of more than 500 with the green light indicator lighting the Buzzer does not emit noise then the conditions are not rainy or can be meant the weather is medium bright, then the sensor value is less than 500 by the indicator Buzzer on then emits the sound and the red lighting indicator color lighting, then indicates the rain condition.